Clinical relevance and outcome of familial papillary thyroid cancer: a single institution study of 626 familial cases - Li, Zhuyao; Zhang, Hongri; Yan, Yu; Li, Xiang; Jia, Meng; Zhou, Honglong; Lu, Xiubo (Frontiers in Endocrinology, 2023)
Background: Whether familial thyroid cancer is more aggressive than sporadic thyroid cancer remains controversial. Additionally, whether the number of affected family members affects the prognosis is unknown. This study focused mainly on the comparison of the clinicopathological characteristics and prognoses between papillary thyroid cancer (PTC) patients with and without family history.Methods: A total of 626 familial papillary thyroid cancer (FPTC) and 1252 sporadic papillary thyroid cancer (SPTC) patients were included in our study. The clinical information associated with FPTC and SPTC was recorded and analyzed by univariate analysis.Results: Patients in the FPTC group had a higher rate of multifocality (p=0.001), bilaterality (p=0.000), extrathyroidal invasion (p=0.000), distant metastasis (p=0.012), lymph node metastasis (p=0.000), recurrence (p=0.000), a larger tumor size (p=0.000) and more malignant lymph nodes involved (central: p=0.000; lateral: p=0.000). In addition, our subgroup analysis showed no significant difference (p>0.05) between patients with only one affected family member and those with two of more group in all clinicopathological characteristics. In papillary thyroid microcarcinoma (PTMC) subgroup analysis, we found that FPTMC patients harbored significantly larger tumors (p=0.000), higher rates of multifocality (p=0.014), bilaterality (p=0.000), distant metastasis (p=0.038), lymph node metastasis (p=0.003), greater numbers of malignant lymph nodes (central: p=0.002; lateral: p=0.044), higher rates of I-131 treatment (p=0.000) and recurrence (p=0.000) than SPTMC patients.Our results indicated that PTC and PTMC patients with a positive family history had more aggressive clinicopathological behaviors, suggesting that more vigilant screening and management for FPTC may be helpful.